A carbon aerogel with super mechanical and sensing performances for wearable piezoresistive sensors. Issue 14 (20th March 2019) - Zhuo, Hao; Hu, Yijie; Chen, Zehong; Peng, Xinwen; Liu, Linxiang; Luo, Qingsong; Yi, Jiwang; Liu, Chuanfu; Zhong, Linxin
Abstract : A compressible carbon aerogel with not only super mechanical performances but also ultrahigh linear sensitivity is fabricated from MXene nanosheets and cellulose nanocrystals (CNCs). Abstract : 3D carbon aerogels with high compressibility and elasticity hold great promise for applications in piezoresistive sensors and various wearable devices. MXenes are new 2D conductive alternatives to fabricate piezoresistive carbon aerogels. However, it's difficult to obtain MXene-based continuous macrostructures with individually lying MXene nanosheets due to their low aspect ratio. To solve this issue, cellulose nanocrystals (CNCs) are used as a nano-support to connect MXene nanosheets into a lamellar carbon aerogel with not only super mechanical performances but also ultrahigh linear sensitivity. The interaction between MXene and CNCs results in a super stable wave-shaped lamellar architecture that can undergo an extremely high compression strain of 95% and long-term compression (10 000 cycles, at 50% strain). It also displays both extremely high sensitivity (114.6 kPa −1 ) and wide linear range (50 Pa–10 kPa) that have not been achieved in other carbon aerogels. In addition, the aerogel can detect a tiny pressure change (1.0 Pa). These advantages allow the carbon aerogel to have application in wearable piezoresistive devices for detecting biosignals.